Respon Kembang Kol Dataran Rendah Terhadap Kepekatan Nutrisi pada Floating Hydroponic System Termodifikasi - Astri Rovi'ati; Endang Setia Muliawati; Dwi Harjoko (Agrosains : Jurnal Penelitian Agronomi, 2019)
Cauliflower has a high consumption level but its production is limited to its region in the highlands and the planting season. An effort to increase its production outside the highland in all seasons is using hydroponics on tolerant varieties. Selection of varieties and giving the right amounts of nutrients will optimize the production of lowland cauliflower. This study aims to determine the types of varieties and concentration of nutrient solution suitable for the cultivation of hydroponic cauliflower in the lowlands. This research uses a Completely Randomized Design (CRD) which consists of 2 factors namely varieties and nutrient solution concentration level with 9 combination treatments and each treatment consisted of 4 plants. The results showed that variety of Mona and  PM 126 are better than the Diamond in the hydroponic cultivation of cauliflower in the lowlands. Concentrations of the nutrient solution did not improve growth and show no significant results, so nutrient solution from EC 2.2 to 2.4 mS/cm is better in the hydroponic cultivation of cauliflower in the lowlands.